Thin Film Metal Nanocluster Light‐Emitting Devices. (20th December 2013) - Niesen, Bjoern; Rand, Barry P.
<x xml:space="preserve">Abstract</x> Light‐emitting devices that utilize thin films of metal nanoclusters as quantum emitters are presented. Implementing Ag as well as Au nanoclusters, the versatility of the approach is demonstrated, and it is shown that the electroluminescence measured from these devices is tunable by the choice of nanocluster. Ultimately, it is demonstrated that metal nanoclusters represent an additional option for future light‐generating applications. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>